Preclinical immunogenicity of an adenovirus-vectored vaccine for herpes zoster. Issue 1 (31st December 2023) - Ulaszewska, Marta; Merelie, Sarah; Sebastian, Sarah; Lambe, Teresa
ABSTRACT: Herpes zoster (HZ) results from waning immunity following childhood infection with varicella zoster virus (VZV) but is preventable by vaccination with recombinant HZ vaccine or live HZ vaccine (two doses or one dose, respectively). Vaccine efficacy declines with age, live HZ vaccine is contraindicated in immunosuppressed individuals, and severe local reactogenicity of recombinant HZ vaccine is seen in up to 20% of older adults, indicating a potential need for new vaccines. Nonreplicating chimpanzee adenovirus (ChAd) vectors combine potent immunogenicity with well-established reactogenicity and safety profiles. We evaluated the cellular and humoral immunogenicity of ChAdOx1 encoding VZV envelope glycoprotein E (ChAdOx1-VZVgE) in mice using IFN-γ ELISpot, flow cytometry with intracellular cytokine staining, and ELISA. In outbred CD-1 mice, one dose of ChAdOx1-VZVgE (1 × 10 7 infectious units) elicited higher gE-specific T cell responses than two doses of recombinant HZ vaccine (1 µg) or one dose of live HZ vaccine (1.3 × 10 3 plaque-forming units). Antibody responses were higher with two doses of recombinant HZ vaccine than with two doses of ChAdOx1-VZVgE or one dose of live HZ vaccine. ChAdOx1-VZVgE boosted T cell and antibody responses following live HZ vaccine priming. The frequencies of polyfunctional CD4+ and CD8+ T cells expressing more than one cytokine (IFN-γ, TNF-α and IL-2) were higher with ChAdOx1-VZVgE than with the conventional vaccines. Results were similar in young and aged BALB/c mice. These findings support the clinical development of ChAdOx1-VZVgE for prevention of HZ in adults aged 50 years or over, including those who have already received conventional vaccines.